Eyelid malpositions: An overview - Marian Pauly (Kerala Journal of Ophthalmology, 2017)
Eyelid malpositions are the result of forces acting upon the eyelid margin. A normal eyelid should have a quick return snap to the eyeball. Frequently, tendon laxity at the medial and lateral canthi will render the eyelid margin unstable making it susceptible to contractile forces. Based on the contractile forces either entropion, ectropion, retraction or lagophthalmos can occur. The goal in treating a given eyelid malposition is to reposition the eyelid so that the new healing forces will overcome the pathologic forces. The common approaches include eyelid and canthal tendon tightening, eyelid retractor advancement or recession and skin grafting or transposition flaps. This review article briefly describes the various aspects of lid malpositions in detail.